Penerapan Metode CSI untuk Pengukuran Tingkat Kepuasan Layanan Manajemen - Haevah Reza Amri; Ridho Taufiq Subagio; Kusnadi (APIC, 2020)
Catur Insan Cendekia University is one of the Universities in Cirebon that always strives to maintain and improve quality in order to compete with other universities. To guarantee quality and improve management services, it is necessary to analyze user satisfaction with management services that are tailored to their wants and needs. CIC University has not conducted an assessment relating to the level of satisfaction of the Academic Community of management services provided. Where there is no measurement of academic service satisfaction by students and general users as well as a system of governance and governance by lecturers and education personnel. It is important to know in order to provide input to the leaders of CIC University, so that they can provide a proposal or improvement in improving management services in order to improve the quality of CIC University. This study discusses management service assessment at CIC University by using UML as a tool in analysis and design, as well as the PHP Hypertext Preproccessor programming language with the CodeIgniter framework, and MySQL as a data storage medium. Data collection is done by filling out the E-Questionnaire where the calculation of the results of the questionnaire is done using the CSI method and testing is done by the Black Box method. The results of this study are the Management Services Assessment Application at CIC University which aims to determine the level of satisfaction of the Academic Community to the performance of management services at CIC University.